What Is On the Horizon for the Diagnosis and Treatment of SCLC and Large Cell Neuroendocrine Cancer? - Sun Min Lim, MD, PhD; Joo Sung Gabriel Shim, MD; Hyo Sup Shim, MD, PhD; Junko Tanizaki, MD, PhD; Jorn Nutzinger, MD; Byoung Chul Cho, MD, PhD; Ross A. Soo, MBBS, PhD (JTO Clinical and Research Reports)
SCLC is a high-grade neuroendocrine malignancy associated with poor prognosis, comprising 15% of lung cancer cases globally. Advances in genetic profiling have revealed that SCLC is a molecularly heterogeneous disease, categorized into subtypes such as SCLC-A, SCLC-N, SCLC-P, and SCLC-I, on the basis of their neuroendocrine and immune-related characteristics. This heterogeneity underscores the need for tailored therapeutic strategies.Large cell neuroendocrine carcinoma (LCNEC) shares histologic and molecular similarities with SCLC but remains a distinct entity. LCNEC is categorized into two major subtypes: Type I, characterized by STK11 and KEAP1 mutations and a neuroendocrine phenotype, and Type II, defined by TP53 and RB1 alterations with higher proliferative indices. LCNEC's rarity and molecular diversity present challenges for standardized treatment, further highlighting the need for comparative research with SCLC.In this review, we highlight the genetic and clinicopathologic features of SCLC and LCNEC. Furthermore, we discuss emerging therapeutics and future directions in the treatment of SCLC and LCNEC.